PECULIARITIES OF ORGANIZING MUSIC LESSONS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Unique features of the organization of music education at school. According to the Law of the Republic of Uzbekistan "On Education", all educational activities are based on the principles of democratization, individualization of education, consideration of regional characteristics. A teaching concept was developed for subjects, including music.